2004
DOI: 10.1063/1.1819556
|View full text |Cite
|
Sign up to set email alerts
|

PVDF sensor in laser ablation experiments

Abstract: This article presents the use of piezoelectric PVDF films as a sensor for the vapor stream in laser ablation experiments. The analysis of the PVDF electric signal gives the translational temperature and the vapor drift velocity of the ablated plume. A PVDF sensor was used in a tungsten ablation experiment, using HyBrID copper laser, and it was obtained a translational temperature of 9×104 K and a drift velocity of 4×105 cm/s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
2
0
3
Order By: Relevance
“…Gião et al 12 reported in detail the use of a PVDF film to monitoring laser ablated plumes. It was used in this work because it allows to monitor both neutral and ions with one single device.…”
Section: Methodsmentioning
confidence: 99%
“…Gião et al 12 reported in detail the use of a PVDF film to monitoring laser ablated plumes. It was used in this work because it allows to monitor both neutral and ions with one single device.…”
Section: Methodsmentioning
confidence: 99%
“…Торсионный маятник 10 -6 …10 -3 10 -6 (10 -9 ) Тензоэлектрический датчик Более 10 -5 10 -6 …10 -5 10 -6 …10 -5 1 [4,12] Пьезоэлектрический датчик Более 10 -5 10 -6 …10 -5 10 -7 …10 -6 1-2 [5,[54][55][56][57][58] Оптодинамический метод 10 -5 10 -7 10 -6 …10 -5 2 [62,63] Комбинированная интерферометрия 10 -11 …10 -4 10 -12 …10 -10 10 -13 …10 -10 3 [3, 70] VISAR 10 -9 …10 -3 10 -9 10 -8 2 [26,71,72] Косвенные измерения (скорость + массовый расход)…”
Section: оценка величины рабочего диапазона I чувствительности δI вunclassified
“…Введение. Для регистрации оптико-механических характеристик при лазерной абляции используется ряд методов, регистрирующих непосредственно механический импульс (баллистические [1] и торсионные [2] маятники, метод комбинированной интерферометрии [3]), силу (тензоэлектрические [4] и МЭМС-датчики силы и момента) и давление (пьезоэлектрические датчики [5]) отдачи на поверхности аблирующей мишени, возникающие в результате генерации светоэрозионного паро-газоплазменного потока. Данные об эффективности генерации импульса отдачи важны для разработки технологий лазерно-плазменных инжекторов [6], ускорителей [7] и двигателей [8], установок лазерного термоядерного синтеза [9], а также для понимания процессов лазерной абляции в целом [10].…”
unclassified
See 1 more Smart Citation
“…The sensor was connected to a digital oscilloscope through a 1 M impedance to ensure proportionality of voltage to pressure. 21 The PVDF transducer sensitivity was 85 mV/MPa and the response time was measured to be 30 ns. However, one disadvantage is that pressure cannot be measured closer than 1 mm to the beam focus position without risking damage to the transducer.…”
Section: Piezoelectric Sensorsmentioning
confidence: 99%